Novel multiple access for cooperative networks with nakagami-m fading: system model and performance analysis - Tu-Trinh Thi Nguyen; Dinh-Thuan Do (Institute of Advanced Engineering and Science, 2020)
This study considers the performances of a downlink non-orthogonal multiple access (NOMA) network over Nakagami-m fading channels. This scheme employs two hop transmission. We first examine the analytical outage probability expression for each user and then these results are verified by Monte Carlo simulations. Based upon the outage probability, the maximal throughput are obtained and analyzed under different parameters. Furthermore, the effects of Nakagami-m channel fading on the probability and throughput are investigated. The results indicate that the performance of the NOMA system is excellent as appropriate selection of simulated parameters. This analysis can be recommended for designing the NOMA systems in the future fifth-generation wireless communication.